Getting CD19 Into Shape: Expression of Natively Folded “Difficult-to- Express” CD19 for Staining and Stimulation of CAR-T Cells - Lobner, Elisabeth; Wachernig, Anna; Gudipati, Venugopal; Mayrhofer, Patrick; Salzer, Benjamin; Lehner, Manfred; Huppa, Johannes B.; Kunert, Renate (Frontiers in Bioengineering and Biotechnology, 2020)
The transmembrane protein CD19 is exclusively expressed on normal and malignant B cells and therefore constitutes the target of approved CAR-T cell-based cancer immunotherapies. Current efforts to assess CAR-T cell functionality in a quantitative fashion both in vitro and in vivo are hampered by the limited availability of the properly folded recombinant extracellular domain of CD19 (CD19-ECD) considered as “difficult-to-express” (DTE) protein. Here, we successfully expressed a novel fusion construct consisting of the full-length extracellular domain of CD19 and domain 2 of human serum albumin (CD19-AD2), which was integrated into the Rosa26 bacterial artificial chromosome (BAC) vector backbone for generation of a recombinant CHO-K1 production cell line. Product titers could be further boosted using valproic acid (VPA) as a chemical chaperone. Purified monomeric CD19-AD2 proved stable as shown by non-reduced SDS-PAGE and SEC-MALS measurements. Moreover, flow cytometric analysis revealed specific binding of CD19-AD2 to CD19-CAR-T cells. Finally, we demonstrate biological activity of our CD19-AD2 fusion construct as we succeeded in stimulating CD19-CAR-T cells effectively with the use of CD19-AD2-decorated planar supported lipid bilayers (SLBs).